Prognostic value of FIB-4 and NFS for cardiovascular events in patients with and without NAFLD - Jun Zhang; Lin Li; Ling Lin; Yifan Wu; Lifen Hu; Zhaolan Feng; Deju Zhang; Taoli Fu; Huilei Zhao; Xiaoping Yin; Peng Yu; Xiang Gu; et al. (BMC Public Health)
Abstract Background The association between non-alcoholic fatty liver disease (NAFLD) and cardiovascular disease (CVD) is well studied. Liver fibrosis is the main histopathologic manifestations of NAFLD. However, whether concomitant NAFLD influence the association of non-invasive liver fibrosis scores with CVD remains unclear. Methods We systematically searched PubMed, Cochrane Library, and Embase databases for cohort studies exploring the association between liver fibrosis score (LFS)and CVD events up to June 10, 2025. Random-effects model was used to pool results. CVD events were defined as cardiovascular mortality, myocardial infarction, and coronary heart disease. Results Nineteen cohorts involving 1,481,875 adults were included with an average age of 54.8 years old, and 50.2% males. Fibrosis 4 score (FIB-4), nonalcoholic fatty liver disease fibrosis score (NFS) and APRI (Aspartate transaminase/platelet ratio index) were associated with increased risks of CVD events (FIB-4: odds ratio [OR] 1.77, 95% confidence interval [CI] 1.58–1.99, low certainty; NFS: OR 2.40, 95% CI 1.83–3.14, low certainty; APRI: OR 1.61, 95% CI 1.17–2.21, low certainty). Each one-unit increment in FIB-4, NFS scores was associated with CVD events (FIB-4: OR 1.21, 95% CI 1.12–1.31; NFS: OR 1.38, 95% CI: 1.17–1.62). A positive linear relationship was observed between FIB-4 (P-nonlinearity = 0.000), NFS (P-nonlinearity = 0.7145) and CVD events. Risk estimates for cardiovascular events were similar in patients with NAFLD (FIB-4: OR 1.87, 95% CI 1.53–2.28; NFS: OR 2.59, 95% CI 1.55–4.33) and without NAFLD (FIB-4: OR 1.74, 95% CI 1.51-2.00; NFS: OR 2.26, 95% CI 1.64–3.11) (P for difference: FIB-4 = 0.56; NFS = 0.66). Conclusion FIB-4 and NFS were associated with an increased risk of CVD events in patients with and without NAFLD. FIB-4 and NFS risk estimates for cardiovascular events were not influenced by concomitant NAFLD. Registration URL: http://www.crd.york.ac.uk/prospero/ PROSPERO (registration number: CRD42023421092). Graphical Abstract